Analisis Sebaran Emisi Total Suspended Particulate Menggunakan Software Aermod di Jalan Raya Tandes - Aditya Rizky Dwicahya; Okik Hendriyanto Cahyonugroho (Jurnal Serambi Engineering, 2024)
Increased transportation activities in this city cause air pollutant emissions, one of which is Total Suspended Particulate (TSP), which has an impact on air quality. This study aims to measure TSP concentration and map its distribution. Data on TSP concentration, air temperature, wind speed, and air humidity were collected using instruments such as High Volume Air Sampler (HVAS), hygrometer, and anemometer. TSP concentrations were modeled with AERMOD based on the obtained data and associated meteorologicalconditions. The results showed that TSP concentrations varied significantly depending on traffic volume and weather, with the highest concentration of 184.8 μg/m3 at point 1 on the first day and the lowest of 9.7 μg/m3 at point 5 on the second day. The distribution of TSP tended to the Southeast, West, and North according to the AERMOD model. Questionnaire results in the sampling areas show that there are still people who are not aware of the impact of TSP pollutants. The conclusion of this study is the presence of TSP pollutants on Tandes Highway, which is influenced by meteorological factors and traffic volume